Gut inflammation markers, diet, and risk of islet autoimmunity in Finnish children – a nested case-control study - Salo, Tuuli E. I. (Elsevier, 2025)
Background: Gut dysbiosis and increased intestinal permeability have been reported to precede type 1 diabetes-related autoimmunity. The role of gut inflammation in autoimmunity is not understood.
Objectives: This study aimed to assess whether gut inflammation markers are associated with risk of islet autoimmunity and whether diet is associated with gut inflammation markers.
Methods: A nested case-control sample of 75 case children with islet autoimmunity and 88 control children was acquired from the Finnish Type 1 Diabetes Prediction and Prevention cohort. Diet was assessed with 3-d food records, and calprotectin and human β-defensin-2 (HBD-2) were analyzed from stool samples at 6 and 12 mo of age. Conditional logistic regression analysis was used in a matched case-control setting to assess risk of autoimmunity. Analysis of variance, independent samples t test, and a general linear model were used in secondary analyses to test associations of background characteristics and dietary factors with inflammation markers.
Results: In unadjusted analyses, calprotectin was not associated with risk of islet autoimmunity, whereas HBD-2 in the middle (odds ratio [OR]: 3.23; 95% confidence interval [CI]: 1.03, 10.08) or highest tertile (OR: 3.02; 95% CI: 1.05, 8.69) in comparison to the lowest at 12 mo of age showed borderline association (P-trend = 0.063) with higher risk of islet autoimmunity. Excluding children with cow milk allergy in sensitivity analyses strengthened the association of HBD-2 with islet autoimmunity, whereas adjusting for dietary factors and maternal education weakened it. At age 12 mo, higher fat intake was associated with higher HBD-2 (β: 0.219; 95% CI: 0.110, 0.328) and higher intake of dietary fiber (β: -0.294; 95% CI: -0.510, -0.078), magnesium (β: -0.036; 95% CI: -0.059, -0.014), and potassium (β: -0.003; 95% CI: -0.005, -0.001) with lower HBD-2.
Conclusions: Higher HBD-2 in infancy may be associated with higher risk of islet autoimmunity. Dietary factors play a role in gut inflammatory status.